2020
DOI: 10.3390/molecules25163720
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Glycosylation of Smoke-Derived Volatile Phenols by Cabernet Sauvignon Grapes and Their Subsequent Fate during Winemaking

Abstract: Wine made from grapes exposed to bushfire smoke can exhibit unpleasant smoky, ashy characters, which have been attributed to the presence of smoke-derived volatile phenols, in free or glycosylated forms. Here we report the uptake and glycosylation of volatile phenols by grapes following exposure of Cabernet Sauvignon vines to smoke, and their fate during winemaking. A significant delay was observed in the conversion of volatile phenols to their corresponding glycoconjugates, which suggests sequestration, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
105
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(127 citation statements)
references
References 32 publications
20
105
2
Order By: Relevance
“…Low levels of VP glycosides (<25 µg/kg) were detected in control grapes, irrespective of any O 3 treatment, in agreement with previous studies which report VP glycosides as natural constituents of some grape varieties [ 11 , 13 , 41 ]. Grapevine exposure to smoke resulted in significantly higher levels of VP glycosides, particularly glycosides of guaiacol, phenol, cresols and syringol ( Table 1 ), for which pentose glucosides of guaiacol, phenol and cresol and the glucose glucoside (gentiobioside) of syringol were most abundant ( Table S1 ), again in agreement with previous research [ 18 , 42 , 43 ]. Statistically significant compositional differences were observed amongst smoke-affected grape samples.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Low levels of VP glycosides (<25 µg/kg) were detected in control grapes, irrespective of any O 3 treatment, in agreement with previous studies which report VP glycosides as natural constituents of some grape varieties [ 11 , 13 , 41 ]. Grapevine exposure to smoke resulted in significantly higher levels of VP glycosides, particularly glycosides of guaiacol, phenol, cresols and syringol ( Table 1 ), for which pentose glucosides of guaiacol, phenol and cresol and the glucose glucoside (gentiobioside) of syringol were most abundant ( Table S1 ), again in agreement with previous research [ 18 , 42 , 43 ]. Statistically significant compositional differences were observed amongst smoke-affected grape samples.…”
Section: Resultssupporting
confidence: 90%
“…However, it be noted that due to windy conditions being experienced on the second day of application, fruit was exposed to less dense smoke, such that VPs were higher in treated with 1 ppm of O3, than with 3 ppm of O3 (Figure 2, Table S6). Elevated con tions of VPs were nevertheless detected in grapes as a consequence of post-harvest exposure; guaiacol and syringol were the most abundant VPs present, and 4-methy Numerous studies have demonstrated that following their uptake from smoke into grapes, VPs accumulate in glycoconjugate forms due to rapid in vivo glycosylation [8,18,43,60,61]. As such, when post-harvest O 3 treatments were applied in the first trial, smoke-derived VPs were only present in glycoconjugate forms ( Table 1 and Table S1).…”
Section: Vps and Vp Glycosidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Summary of the methods evaluated for prevention of smoke taint in the vineyard.Washing vines or grapes with water, aqueous ethanol, or milk after smoke exposure did not affect the guaiacol content of grapes or juice. Misting grapes during smoke exposure partially mitigated the uptake of volatile phenols by grapes but did not influence the perception of smoke taint in wine[29,40,55].…”
mentioning
confidence: 99%